1995
DOI: 10.1002/jcc.540160104
|View full text |Cite
|
Sign up to set email alerts
|

Propella[34] prismane and its congeners: A MO‐theoretical study

Abstract: The geometries of a fourfold bridged tricycle[ 4.2.0.02,5]octa-3,7-diene (1) and its photoproducts 2 and 3 were calculated by Hartree-Fock ab initio (3-21G and DZP basis) and semiempirical (MNDO, AM1, MIND0/3) methods. It wss found that due to the smaller distance between the double bond2 in 1 (2.65 A) as compared to the parent tricyclo[4.2.0.02~5]octa-3,7-diene (4) (2.91 A), the sequence of the frontier orbitals is different. In the case of 1, the photochemical [2 + 2]cycl.oaddition is allowed, whereas in 4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…16 Gleiter also demonstrated that one could achieve the [2+2]photocycloaddition of 1 by shortening the intramolecular π-π distance (Δr = 0.3 Å) with tethered propyl bridges (-CH2CH2CH2-), which lowers the πSS to HOMO-1, thus restoring the requisite orbital-symmetry to allow the [2+2]-photocycloaddition. 15 5), 17 octa(trifluoromethyl)cubane (8), 18 and octacyclopropylcubane (11). 19 The correlation diagrams for the [2+2]-cycloadditions of substituted [3]-ladderenes (i.e., 4, 7, and 10) are qualitatively similar and suggest that this pathway is symmetry-forbidden.…”
Section: Introductionmentioning
confidence: 95%
“…16 Gleiter also demonstrated that one could achieve the [2+2]photocycloaddition of 1 by shortening the intramolecular π-π distance (Δr = 0.3 Å) with tethered propyl bridges (-CH2CH2CH2-), which lowers the πSS to HOMO-1, thus restoring the requisite orbital-symmetry to allow the [2+2]-photocycloaddition. 15 5), 17 octa(trifluoromethyl)cubane (8), 18 and octacyclopropylcubane (11). 19 The correlation diagrams for the [2+2]-cycloadditions of substituted [3]-ladderenes (i.e., 4, 7, and 10) are qualitatively similar and suggest that this pathway is symmetry-forbidden.…”
Section: Introductionmentioning
confidence: 95%
“…The [2 + 2] photocycloaddition of unsubstituted tricyclo­[4,2,0,0 2,5 ]­octa-3,7-dienes ( 1 ) has not been experimentally reported. Gleiter and co-workers found the [2 + 2] photocycloaddition via the lowest-energy photoexcitation of 1 is symmetry forbidden using then-contemporary methods such as AM1 and Hartree–Fock with the 3-21G basis set. Through-space orbital interactions between the π- and σ-orbitals of the tricyclic framework were shown to rearrange the frontier molecular orbitals (FMOs) as shown in Scheme . , Gleiter explains that the lowest-energy transition in the TOD precursor of propellacubane (Scheme ) is symmetry-allowed because the reduced through-bond interactions lead to rearranged FMOs and an observed [2 + 2] photocycloaddition. ,, …”
Section: Introductionmentioning
confidence: 99%
“…22 The [2 + 2] photocycloaddition of unsubstituted tricyclo-[4,2,0,0 2,5 ]octa-3,7-dienes (1) has not been experimentally reported. Gleiter and co-workers found the [2 + 2] photocycloaddition via the lowest-energy photoexcitation of 1 is symmetry forbidden 23 using then-contemporary methods such as AM1 24 and Hartree−Fock with the 3-21G basis set. Through-space orbital interactions between the πand σorbitals of the tricyclic framework were shown to rearrange the frontier molecular orbitals (FMOs) as shown in Scheme 2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Through-space orbital interactions between the π-and σ-orbitals of the tricyclic framework were shown to rearrange the frontier molecular orbitals (FMOs) as shown in Scheme 2. 16 Gleiter explains that the lowest-energy transition in the TOD precursor of propellacubane (Scheme 1) is symmetry-allowed because the reduced through-bond interactions lead to rearranged FMOs and an observed [2+2] photocycloaddition. 16,18 Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…16 Gleiter explains that the lowest-energy transition in the TOD precursor of propellacubane (Scheme 1) is symmetry-allowed because the reduced through-bond interactions lead to rearranged FMOs and an observed [2+2] photocycloaddition. 16,18 Scheme 2. Frontier molecular orbitals diagram of 1.…”
Section: Introductionmentioning
confidence: 99%